Personality Changes after Deep Brain Stimulation in Parkinson’s Disease - Uyen Pham; Anne-Kristin Solbakk; Inger-Marie Skogseid; Mathias Toft; Are Hugo Pripp; Ane Eidahl Konglund; Stein Andersson; Ira Ronit Haraldsen; Dag Aarsland; Espen Dietrichs; Ulrik Fredrik Malt (Parkinson's Disease)
Objectives. Deep brain stimulation of the subthalamic nucleus (STN-DBS) is a recognized therapy that improves motor symptoms in advanced Parkinson’s disease (PD). However, little is known about its impact on personality. To address this topic, we have assessed personality traits before and after STN-DBS in PD patients. Methods. Forty patients with advanced PD were assessed with the Temperament and Character Inventory (TCI): the Urgency, Premeditation, Perseverance, Sensation Seeking impulsive behaviour scale (UPPS), and the Neuroticism and Lie subscales of the Eysenck Personality Questionnaire (EPQ-N, EPQ-L) before surgery and after three months of STN-DBS. Collateral information obtained from the UPPS was also reported. Results. Despite improvement in motor function and reduction in dopaminergic dosage patients reported lower score on the TCI Persistence and Self-Transcendence scales, after three months of STN-DBS, compared to baseline (P=0.006; P=0.024). Relatives reported significantly increased scores on the UPPS Lack of Premeditation scale at follow-up (P=0.027). Conclusion. STN-DBS in PD patients is associated with personality changes in the direction of increased impulsivity.